Work with campus safety officials to keep students with autism safe. Issue 1 (16th July 2018) - Hope, Joan
Abstract : Individuals on the autism spectrum are statistically more likely to have contact with law enforcement than others. In fact, by some estimates, they are seven times as likely to have contact with law enforcement officers compared with their neurotypical peers. These contacts can occur because individuals with autism spectrum disorder might behave in ways that arouse suspicion, or they might behave inappropriately because they don't understand social expectations. And people with ASD are at high risk of becoming victims. In fact, they are more likely to be victims than criminals, said Dennis Debbaudt, who provides training to police departments on working with individuals on the spectrum through his business Autism Risk and Safety Management.